Online English Teaching and Learning in Higher Education: Lessons from Chinese College Students - Han, Wei; Apridayani, Aisah; Tang, Yuling; Mukrim, Mukrim (Journal of Education Culture and Society, 2024)
Aim. The current study aims to investigate Chinese students’ perceptions and experiences with online English learning, as well as their recommendations for future online English courses. Methods. This study included 383 Chinese college students and was conducted using a mixed-methods, sequential explanatory research design. A survey questionnaire and semi-structured interviews were used to collect data from the students. The collected data was analyzed both statistically and thematically. Results. The findings provided useful insights into the strengths and areas for improvement in current online English learning practices. Despite widespread comfort and satisfaction with online learning platforms, concerns about the digital divide, engagement, interactivity, and assessment integrity call for a more nuanced approach to online course design and delivery. Conclusion. Students highlighted several recommendations for future online English learning, including a desire for more interactive sessions, better management of student needs, diversification of learning activities, emotional support and motivation, and enhancing online exam integrity. Cognitive value. This study offers some pedagogical implications for infrastructure, the learning environment, teaching methods, and approaches to online assessments. It also advocates for a rethinking of how online courses are designed and taught to meet the changing needs of students in the digital age.